2006
DOI: 10.1242/jcs.03078
|View full text |Cite
|
Sign up to set email alerts
|

Conserved and specific functions of axoneme components in trypanosome motility

Abstract: The Trypanosoma brucei flagellum is unusual as it is attached along the cell body and contains, in addition to an apparently conventional axoneme, a structure called the paraflagellar rod, which is essential for cell motility. Here, we investigated flagellum behaviour in normal and mutant trypanosome cell lines where expression of genes encoding various axoneme proteins (PF16, PF20, DNAI1, LC2) had been silenced by RNAi. First, we show that the propulsive wave (normally used for forward motility) is abolished … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
261
2
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(296 citation statements)
references
References 80 publications
(91 reference statements)
27
261
2
5
Order By: Relevance
“…S5). However, in contrast to a previous study that showed outer dynein arms were often missing in cells depleted of PF16 (42), the outer doublets retained the full complement of outer dynein arms (Fig. 6E).…”
Section: Tz and Ciliary Subdomains Defined By Protein Localization Usingcontrasting
confidence: 99%
See 2 more Smart Citations
“…S5). However, in contrast to a previous study that showed outer dynein arms were often missing in cells depleted of PF16 (42), the outer doublets retained the full complement of outer dynein arms (Fig. 6E).…”
Section: Tz and Ciliary Subdomains Defined By Protein Localization Usingcontrasting
confidence: 99%
“…6 E and H). Similar to PF16 knockdown studies (42), loops of flagellum detachment from the cell body were observed, as were defects in the flagellum-cell body attachment apparatus ( Fig. 6G and Fig.…”
Section: Tz and Ciliary Subdomains Defined By Protein Localization Usingsupporting
confidence: 74%
See 1 more Smart Citation
“…Although of a low frequency (3% of all cells, n = 16 of 518), this phenotype is significant, because we did not observe similar cells in wild-type cultures. These cells were likely products of an uncompleted cytokinesis and resemble a phenotype observed in flagella motility mutants (28,29).…”
Section: Immunogold Em Labeling Sublocalizes Proteins To Specific Tipmentioning
confidence: 75%
“…4), outer dynein arms (Fig. 5), dynein regulatory complex and protofilament ribbons demonstrated a requirement for each of these structures in T. brucei flagellar motility (Ralston et al, 2005Branche et al, 2006;Baron et al, 2007a). See Table 1 for a complete list of these proteins, as well as other characterized components of the T. brucei flagellum.…”
Section: Axonemementioning
confidence: 99%